2002
DOI: 10.1097/00007890-200208270-00009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of viral DNA in renal allograft tissue from patients with BK virus nephropathy1

Abstract: BKV load exceeding 59 copies per cell identified all cases of BKVAN. The diagnostic sensitivity, specificity, positive predictive value, and negative predictive value of quantitative PCR were 100%, 92.1%, 73.6%, and 100%, respectively. Lower levels of BKV DNA were identified in biopsies performed before viral nephropathy development. Future research will determine if earlier recognition of at-risk patients allows application of antiviral strategies to improve graft outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 15 publications
2
59
2
Order By: Relevance
“…Although, like most studies investigating BKVAN, our study was limited by the low number of affected patients, data obtained from our group and those by Randhawa and coll. indicate that the highest BKV load (in both the studies >10 3 copies/cell) are found in renal specimens from patients with active PVAN. The evidence that renal tubules accumulate thousands of viral particles before undergoing cell lysis underlines the role of cytopathic effect in renal allograft injury in PVAN (Randhawa et al, 2002). Considering pre-PVAN, giving the evaluation of only one case, our study failed to evidence a higher viral load in comparison to patients with asymptomatic viruria; alternatively this could be due to to the sampling interval, as specimen was evaluated 2.1 months before the diagnosis of PVAN was made.…”
Section: Discussionmentioning
confidence: 70%
“…Although, like most studies investigating BKVAN, our study was limited by the low number of affected patients, data obtained from our group and those by Randhawa and coll. indicate that the highest BKV load (in both the studies >10 3 copies/cell) are found in renal specimens from patients with active PVAN. The evidence that renal tubules accumulate thousands of viral particles before undergoing cell lysis underlines the role of cytopathic effect in renal allograft injury in PVAN (Randhawa et al, 2002). Considering pre-PVAN, giving the evaluation of only one case, our study failed to evidence a higher viral load in comparison to patients with asymptomatic viruria; alternatively this could be due to to the sampling interval, as specimen was evaluated 2.1 months before the diagnosis of PVAN was made.…”
Section: Discussionmentioning
confidence: 70%
“…Follow-up biopsies were recorded as complete viral clearance, improved, unchanged, or worse compared to the index specimen. In 12 biopsies the tissue viral load was also determined using a published real-time quantitative PCR assay (8). Clinical data were abstracted from the medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with low-dose cidofovir has apparently been useful in a number of cases reported, but no controlled trials have been performed (1,3,10,11). Once therapy has been initiated, quantitative testing for BKV loads has been suggested as a way to monitor the clinical course of infection (5,6,9,11). Relatively limited data are available on how the BKV load correlates with specific phases of disease, namely, active viral nephropathy, histologic resolution, and subclinical viruria.…”
mentioning
confidence: 99%